Peritoneal Dialysis and Mortality, Kidney Transplant, and Transition to Hemodialysis: Trends From 1996-2015 in the United StatesPlain-Language Summary - Nidhi Sukul (Kidney Medicine, 2020)
Rationale & Objective: Transitions between dialysis modalities can be disruptive to care. Our goals were to evaluate rates of transition from peritoneal dialysis (PD) to in-center hemodialysis (HD), mortality, and transplantation among incident PD patients in the US Renal Data System from 1996 to 2015 and identify factors associated with these outcomes. Study Design: Observational registry-based retrospective cohort study. Setting & Participants: Medicare patients incident to end-stage renal disease (ESRD) from January 1, 1996, through December 31, 2011 (for adjusted analyses; through December 31, 2014, for unadjusted analyses), and treated with PD 1 or more days within 180 days of ESRD incidence (n = 173,533 for adjusted analyses; n = 219,787 for unadjusted analyses). Exposure & Predictors: Exposure: 1 or more days of PD. Predictors: patient- and facility-level characteristics obtained from Centers for Medicare & Medicaid Services Form 2728 and other data sources. Outcomes: Patients were followed up for 3 years until transition to in-center HD, death, or transplantation. Analytical Approach: Multivariable Cox regression was used to estimate hazards over time and associations with predictors. Results: Compared with earlier cohorts, recent incident PD patient cohorts had lower rates of death (48% decline) and transition to in-center HD (13% decline). Among many other findings, we found that: (1) rates of transition to in-center HD and death were lowest in the 2008 to 2011 cohort, (2) longer time receiving PD was associated with higher mortality risk but lower risk for transition to in-center HD, and (3) larger PD programs (≥25 vs ≤6 patients) displayed lower risks for death and transition to in-center HD. Limitations: Data collected on Form 2728 are only at the time of ESRD incidence and do not provide information at the time of transition to in-center HD, death, or transplantation. Conclusions: Rates of transition from PD to in-center HD and death rates for PD patients decreased over time and were lowest in PD programs with 25 or more patients. Implications of the observed improved technique survival warrant further investigation, focusing on modifiable factors of center-level performance to create opportunities for improved patient outcomes.